2019
DOI: 10.1002/ejp.1466
|View full text |Cite
|
Sign up to set email alerts
|

Sleep restriction does not potentiate nocebo‐induced changes in pain and cortical potentials

Abstract: Background The increased pain sensitivity following reduced sleep may be related to changes in cortical processing of nociceptive stimuli. Expectations shape pain perception and can inhibit (placebo) or enhance (nocebo) pain. Sleep restriction appears to enhance placebo responses; however, whether sleep restriction also affects nocebo responses remains unknown. The aim of the present study was to determine whether sleep restriction facilitates nocebo‐induced changes in pain and pain‐evoked cortical potentials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…This was first illustrated by the modification of N100 and P200 ERPs components following painful stimulations, and further supported by the significant correlation between those ERPs component and the selfreported level of pain. The relevance of the N100-P200 as an objective measure of pain perception has similarly been highlighted in several studies investigating laserevoked EEG (Matre et al, 2015;Ree et al, 2020).…”
Section: Control Conditionmentioning
confidence: 87%
See 1 more Smart Citation
“…This was first illustrated by the modification of N100 and P200 ERPs components following painful stimulations, and further supported by the significant correlation between those ERPs component and the selfreported level of pain. The relevance of the N100-P200 as an objective measure of pain perception has similarly been highlighted in several studies investigating laserevoked EEG (Matre et al, 2015;Ree et al, 2020).…”
Section: Control Conditionmentioning
confidence: 87%
“…The Digitimer electrical stimulus generator device (DS7A) was kept at 500 μs with 300 V, meaning that the pulse duration was 0.5 ms with a maximum compliance of the stimulation set to 300 V. The electrical pulse intensity calibrated for each subject ranged from 4 to 8 mA. To deliver the first 30 automatically electrical pulse noxious stimuli, the following parameters were set in the electrical pulse generator device (DG2A): pulse mode = free run, repetition: 0.1 Hz (i.e., 10 s of inter‐stimulus interval), delay: 10 ms, output = OUT‐2 (i.e., to deliver the electrical stimulation as a double pulse) (Ree et al, 2020 ). For the last manually delivered electrical pulse noxious stimulation, the following parameters were set: pulse mode = train, delay: 10 ms, output = OUT‐2, and manual inter‐stimulus interval = 10–15 s (Matre et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported increased or unchanged pain ratings, combined with lowered or unchanged time-domain ERPs after sleep restriction compared to habitual sleep ( Matre et al., 2015 ; Odegard et al., 2014 ; Ree et al., 2019 ; Schuh-Hofer et al., 2015 ; Tiede et al., 2010 ). Our results indicate that increased latency jitter after sleep restriction may contribute to the attenuation of averaged ERPs after sleep restriction.…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies of experimental sleep restriction and pain-elicited ERPs have shown that while laser-induced pain ratings were unchanged (Odegard et al, 2014) or increased after sleep restriction (Schuh-Hofer et al, 2015;Tiede et al, 2010), the corresponding ERP amplitude was reduced (Odegard et al, 2014;Schuh-Hofer et al, 2015;Tiede et al, 2010). However, for electrical stimuli, sleep restriction increased pain ratings, but did not change the ERP amplitude (Matre et al, 2015;Ree et al, 2019). These seemingly paradoxical differential effects of sleep restriction on psychophysical and neurophysiological outcome measures need attention.…”
Section: Introductionmentioning
confidence: 99%